RELIGIOUS TOLERANCE IN THE DIGITAL SPACE A STUDY OF HABIB JAFAR'S MESSAGES OF TOLERANCE - Khatami Rahman; Andi Eka Putra; Nofrizal (Religi: Jurnal Studi Agama-agama, 2026)
This study seeks to examine the phenomenon of increasing religious intolerance in Indonesia’s digital sphere, which has affected social interactions and poses a challenge to social harmony within a pluralistic society. This condition highlights the need for an academic investigation into how religious messages that support values of tolerance are articulated and disseminated through new media platforms. The objective of this research is to analyze the construction of religious narratives in the digital content of Habib Husein Ja’far Al Hadar and to examine audience responses to these narratives.The study employs a qualitative approach using content analysis and descriptive methods. Data were collected through observations of YouTube and Instagram content, a review of relevant literature, and an analysis of audience responses within digital spaces. The findings indicate that the religious narratives presented are dialogical, humanistic, and contextual, emphasizing humanitarian values, the diversity of religious experiences, and mutually respectful social relations. Social media and podcast platforms have proven to be effective channels for expanding the reach of these religious narratives, enabling interaction, participation, and rapid dissemination across demographic boundaries. Audience responses, as reflected in comments, expressions of appreciation, and content sharing, demonstrate positive reception and underscore the significant role of these narratives in enhancing awareness of religious diversity within the digital public sphere. These findings affirm that communicative and contextual religious narratives in the digital realm possess strategic potential for fostering a culture of tolerance within pluralistic societies.  Keyword: content analysis, digital dakwah, global ethics, moderation, audience response   Penelitian ini berfungsi untuk menangkap fenomena meningkatnya intoleransi beragama dalam ruang digital Indonesia, yang berdampak pada interaksi sosial dan mengancam keharmonisan dalam masyarakat yang beragam. Situasi ini menciptakan kebutuhan untuk secara akademis mengeksplorasi cara penyampaian pesan agama yang mendukung nilai-nilai toleransi melalui platform media baru. Tujuan penelitian ini adalah menganalisis konstruksi narasi keberagamaan dalam konten digital Habib Husein Ja’far Al Hadar serta respons audiens terhadap narasi tersebut. Penelitian menggunakan pendekatan kualitatif dengan metode analisis isi dan deskriptif. Data diperoleh melalui observasi konten YouTube dan Instagram, telaah literatur, serta analisis respons audiens di ruang digital. Hasil penelitian menunjukkan bahwa narasi keberagamaan yang ditampilkan bersifat dialogis, humanis, dan kontekstual, dengan penekanan pada nilai kemanusiaan, keberagaman pengalaman beragama, serta relasi sosial yang saling menghargai. Media sosial dan podcast telah terbukti menjadi saluran efektif untuk memperluas jangkauan penyebaran narasi keberagaman kontennya, memungkinkan interaksi, partisipasi, serta penyebaran pesan dengan cepat dan melampaui batas demografis. Respons audiens yang terlihat dari komentar, apresiasi, dan berbagi ulang konten menunjukkan penerimaan yang positif dan peran penting pesan tersebut dalam meningkatkan kesadaran akan keberagaman di ruang publik digital. Hasil ini menegaskan bahwa keberagaman yang bersifat komunikatif dan kontekstual di dunia digital memiliki potensi strategis untuk membangun budaya toleransi di tengah masyarakat yang plural. Kata kunci: analisis isi, narasi keberagamaan digital, etika global, moderasi, respons audiens